Government as God's Agent: A Reconsideration of Romans 12 and 13 - Olree, Andy G. (Stone-Campbell journal, 2005)
In the past five years, many evangelical leaders in the United States have been issuing public statements of opinion about public policy in reaction to particular events that have garnered nationwide media attention. Their opinions seem to proceed from longstanding assumptions among many evangelicals about God's will for governments. This article examines those assumptions in light of Romans 12 and 13, concluding that God may well have ordained governments for more limited purposes than these leaders assume.